Knee vs hip single-joint intra-articular hyaluronic acid injection in patients with both hip and knee osteoarthritis: a pilot study - YAĞCI, İLKER (SPRINGER, 2009)
This paper aims to compare the results of single-joint knee vs hip hyaluronic acid (HA) injections in patients with osteoarthritis (OA) involving both the knee and hip joints. Thirty-eight patients who were diagnosed to have both hip and knee OA were enrolled. Patients were divided into two groups to receive HA injection three times at 1-week intervals either to the hip or knee joints. Pain level during activities and rest was measured by using visual analog scale (VAS). Western Ontario and McMaster University Osteoarthritis Index (WOMAC 5-point Likert 3.0) was also used prior to the injections and 1 month after the 3rd injection. In the knee injection group, the intragroup analysis revealed significant improvements in VAS activity pain, VAS rest pain, and WOMAC pain values following injection when compared with preinjection values, while no significant difference was detected in WOMAC stiffness, WOMAC physical function, and WOMAC total values. In the hip injection group, VAS activity pain, VAS rest pain, WOMAC pain, WOMAC stiffness, WOMAC physical function, and WOMAC total values showed significant improvement after the injection when compared with preinjection values. Although statistically not significant (p > 0.05), the comparison of the differences (preinjection-postinjection) between the groups demonstrated higher values in the hip injection group. We imply that intra-articular single-joint HA injections either to the knee or hip joints in OA patients with involvement of both of these joints are effective with regard to pain and functional status.
Keywords: Hip; Hyaluronic acid; Intra-articular injection; Knee; Osteoarthritis; OF-THE-LITERATURE; GENE-EXPRESSION; CRITERIA; RECOMMENDATIONS; CLASSIFICATION; MANAGEMENT; TRIALS